Antithrombotic drug removal from whole blood using Haemoadsorption with a porous polymer bead sorbent. Issue 8 (3rd June 2022) - Tripathi, Ritu; Morales, Jesus; Lee, Victoria; Gibson, C Michael; Mack, Michael J; Schneider, David J; Douketis, James; Sellke, Frank W; Ohman, Magnus E; Thourani, Vinod H; Storey, Robert F; Deliargyris, Efthymios N
Abstract: Aim: To evaluate the ability of the DrugSorb™-AntiThrombotic Removal (ATR) haemoadsorption device utilizing porous polymer bead sorbent technology to remove three commonly used antithrombotic drugs from whole blood. Methods and results: We evaluated the removal of apixaban, rivaroxaban, and ticagrelor by the DrugSorb-ATR haemoadsorption device in a benchtop clinical scale model using bovine whole blood. Blood spiked at clinically relevant concentrations of an antithrombotic agent was continuously circulated through a 300-mL DrugSorb-ATR haemoadsorption device at a flow rate of 300 mL/min. Drug concentration was monitored over 6 h to evaluate drug removal. Results were compared with a control circuit without the haemoadsorption device. Removal rates at 30, 60, 120, and 360 minutes were: apixaban: 81.5%, 96.3%, 99.3% >99.8%; rivaroxaban: 80.7%, 95.1%, 98.9%, >99.5%; ticagrelor: 62.5%; 75%, 86.6%, >95% (all P <0.0001 vs. control). Blood pH and haematological parameters were not significantly affected by the DrugSorb-ATR haemoadsorption device when compared with the control circuit. Conclusion: DrugSorb-ATR efficiently removes apixaban, rivaroxaban, and ticagrelor in a clinical-scale benchtop recirculation circuit with the bulk of removal occurring in the first 60 minutes. The clinical implications of these findings are currently investigated in patients undergoing on-pump cardiothoracic surgery in two US pivotal trials (ClinicalTrials.gov Identifiers: NCT04976530 and NCT05093504).